Capacity building for the documentation and conservation of Latin American cultural heritage: making technology accessible and sustainable. Issue 2 (30th April 2021) - Reina Ortiz, Miquel; Santana Quintero, Mario; Vernaza, Clemencia; Ramírez, Patricia; Montejo Gaitán, Fernando; Segura Escobar, Juana
Abstract : Purpose: The purpose of this contribution is to demonstrate the importance of interdisciplinary collaboration in integrating advanced and emerging digital techniques in the appropriate and sustainable documentation of heritage sites in Latin America. Existing collaboration between the Universidad del Externado de Colombia, the Colombian Institute of Anthropology and History and the Carleton Immersive Media Studio of Carleton University in Ottawa (Canada) have been sued to demonstrate the importance of this approach. The described collaboration allowed a team of students, researchers, government experts and educators to document selected pilot areas of the remarkable UNESCO World Heritage Sites of National Archeological Park of Tierradentro (UNESCO, 1995) and San Agustín Archaeological Park (UNESCO, 1995). The sophisticated digital recording techniques described, such as 3D scanning, aerial and ground photogrammetry techniques, were used to capture the site's current physical condition, emphasizing the pressing need to conserve the threatened mural paintings (Tierraadentro) and carved rock phases (San Agustin). This contribution also underlines the importance of developing the training of emerging professionals from Colombia in adopting these techniques to make their documentation more accurate, reliable and sustainable in the long term. The project's conclusions demonstrate that it is crucial to integrate emerging documentation techniques into the sustainable approach to conservation of these two important UNESCO World Heritage Sites. Design/methodology/approach: The approach presented in this contribution makes technology more accessible to the conservation specialist in Latin America. It provides a comprehensive capacity building program that involves teaching about theory and practice, using two important UNESCO World Heritage Sites located in Colombia. It is also relevant to the interdisciplinary and institutional collaboration between two universities in the North/South areas of the continent and a government institution that effectively collaborates to provide training to emerging professionals. Findings: The contribution summarizes the opportunities and limitations of adopting technology to make the documentation process for conservation more sustainable in low-income economies and provides a framework to implement future strategies in South America. Originality/value: The paper raises a discussion on how the concept of sustainability of adopting new technologies in the context of Latin American countries can assist in optimizing the conservation of decorated surfaces in important UNESCO World Heritage Sites by involving capacity building of emerging professionals.